Effectiveness of Electronic Land Certification Services at the Land Office: A Study at the ATR/BPN Office of Surakarta (Indonesian Journal of Agrarian Law, 2026)
This study discusses the effectiveness of electronic land certificate services at the Surakarta City Land Office. The implementation of electronic certificates is intended to improve legal certainty, efficiency, transparency, and land data security. This study aims to analyze the effectiveness of electronic land certificate services and identify factors influencing their implementation. The research method used is empirical juridical with a qualitative descriptive approach, in which data were obtained through interviews, observations, and document studies involving employees of the Surakarta City Land Office, Land Deed Officials (PPAT), and members of the public who use electronic certificate services. The study employs Soerjono Soekanto’s theory of legal effectiveness, which includes legal substance, law enforcement officials, facilities and infrastructure, public legal awareness, and legal culture. The results indicate that electronic land certificate services in Surakarta City have been implemented well in terms of regulatory support and personnel readiness. However, several obstacles were still identified, such as electronic systems that frequently experience disruptions, server maintenance, relatively lengthy data validation processes, and public doubts regarding digital documents. Nevertheless, electronic certificates provide various benefits, including faster administrative processes, better data integration, minimizing document forgery, and enhancing transparency in land administration services. This study contributes to digital land administration studies by highlighting challenges in implementing electronic certificates at the regional level. Therefore, it is necessary to strengthen technological infrastructure, improve human resource capacity, and conduct public outreach so that electronic land certificate services can operate more optimally and gain public trust.